2012
DOI: 10.1016/j.nanoen.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric properties of copper selenide with ordered selenium layer and disordered copper layer

Abstract: Thermoelectric figure of merit (ZT) of ~1.6 at 700 °C is achieved in β-phase copper selenide . A λ-shaped specific heat peak indicates a phase transition from cubic β-phase to tetragonal α-phase at around 140 °C upon cooling and vice versa. An abnormal decrease in specific heat with increasing temperature was also observed due to the increased random motion of disordered Cu atoms.These features indicate that β-phase Cu 2 Se could be potentially an interesting thermoelectric material, competing with other conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
232
4
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(263 citation statements)
references
References 36 publications
23
232
4
4
Order By: Relevance
“…Nano and micro grain sizes and their distribution in the structure have a strong influence on the TE properties of the compound. K. Comparing the electrical conductivity with the values reported by Gahtori et al [15] and Yu et al [6] , some 15% (≈1000 S/cm) and almost 75% (≈725 S/cm) enhancements are observed at RT, respectively. This might be due to the percolated network of large (micron-sized) grains in the Cu 2 Se_nl compound.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Nano and micro grain sizes and their distribution in the structure have a strong influence on the TE properties of the compound. K. Comparing the electrical conductivity with the values reported by Gahtori et al [15] and Yu et al [6] , some 15% (≈1000 S/cm) and almost 75% (≈725 S/cm) enhancements are observed at RT, respectively. This might be due to the percolated network of large (micron-sized) grains in the Cu 2 Se_nl compound.…”
Section: Resultssupporting
confidence: 69%
“…Copper selenide structures have previously been used in photovoltaic cells and devices [2,3] and are being considered even in biological systems [4] . This renewed interest can be attributed to the low thermal conductivity of the material as well as to its phase changing nature, which is an interesting aspect of the material [5][6][7][8][9][10] . The constituent elements are abundant in nature, and are considered as more benign in comparison to many other TE structures, especially those containing Pb, Sb, As, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The drastic off center behavior indicates inten sive scattering at the Cu site, similar to a rattling atom. This is attributed to the suppression of ionic conduction, as investi gated in the Cu 2 Se system, [124][125][126] which leads to weak bonding between Cu and Se, due to the lack of diffusion path for Cu + ions in the [Cu 2 Se 2 ] 2− layers. Via a projected Grüneisen parame ters calculation, the contributions of Cu and Se are highlighted, rather than the Bi site, as once thought.…”
Section: Bicuseomentioning
confidence: 99%